2022
DOI: 10.14814/phy2.15401
|View full text |Cite
|
Sign up to set email alerts
|

Positive chronotropic action of HCN channel antagonism in human collecting lymphatic vessels

Abstract: Spontaneous action potentials precede phasic contractile activity in human collecting lymphatic vessels. In this study, we investigated the expression of hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels in human collecting lymphatics and by pharmacological inhibition ex vivo tested their potential role in controlling contractile function. Spontaneous and agonist‐evoked tension changes of isolated thoracic duct and mesenteric lymphatic vessels—obtained from surgical patients with informed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Pacemaking in sinoatrial nodal cells of the heart involves HCN channels, Cav1.3 channels, T-type channels, and a RYR2 based Ca 2+ C-clock coupled to the electrogenic Na + –Ca 2+ exchanger ( Yaniv et al, 2015 ; Sirenko et al, 2016 ; Tsutsui et al, 2018 ) to mediate diastolic depolarization. Although HCN2 expression has been detected in lymphatic thoracic duct and mesenteric collectors, it is unlikely that HCN activation is a critical component of pacemaking in lymphatic muscle as inhibition of HCN with ivabradine, ZD7288, or cesium at concentrations selective for HCN channels does not alter chronotropy ( Majgaard et al, 2022 ). Future studies utilizing modern RNAseq to identify other suitable ion channels and confirmation of their functional contributions with patch clamp approaches will assist in revealing the complete ionic mechanisms that contribute to lymphatic muscle pacemaking.…”
Section: Discussionmentioning
confidence: 99%
“…Pacemaking in sinoatrial nodal cells of the heart involves HCN channels, Cav1.3 channels, T-type channels, and a RYR2 based Ca 2+ C-clock coupled to the electrogenic Na + –Ca 2+ exchanger ( Yaniv et al, 2015 ; Sirenko et al, 2016 ; Tsutsui et al, 2018 ) to mediate diastolic depolarization. Although HCN2 expression has been detected in lymphatic thoracic duct and mesenteric collectors, it is unlikely that HCN activation is a critical component of pacemaking in lymphatic muscle as inhibition of HCN with ivabradine, ZD7288, or cesium at concentrations selective for HCN channels does not alter chronotropy ( Majgaard et al, 2022 ). Future studies utilizing modern RNAseq to identify other suitable ion channels and confirmation of their functional contributions with patch clamp approaches will assist in revealing the complete ionic mechanisms that contribute to lymphatic muscle pacemaking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to voltage-gated sodium channels, multiple other channel types, such as Ano1, HCN, and other cationic channels may contribute to the pacemaking and upstroke of lymphatic depolarization. Different from rat (Negrini et al, 2016), sheep (McCloskey et al, 1999) and human (Majgaard et al, 2022) lymphatic vessels—which have HCN-mediated currents—the mRNA expression for HCN was minimal in our murine LMC dataset ( Figure S5F ). Ano1 was present in our dataset ( Figure 3C ), consistent with its known role in LMC depolarization (Zawieja et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The role of HCN channels in lymphatic pacemaking is controversial (McCloskey et al, 1999; Negrini et al, 2016). Studies have demonstrated that they might play a role in human collecting vessels (Majgaard et al, 2022). We did not find strong mRNA expression of HCN genes in LMCs ( Figure S5F ).…”
Section: Resultsmentioning
confidence: 99%
“…Screening of reference lists of included papers yielded an additional seven articles for inclusion. In total, 28 papers (Amann-Vesti et al, 2003;Belgrado et al, 2016;Bell et al, 2020;Gray et al, 2016;Groenlund et al, 2017;Holm-Weber et al, 2022;Kelly, Mohanakumar, Telinius, et al, 2020;Lopera et al, 2017;Majgaard et al, 2022;Modi et al, 2007;Mohanakumar et al, 2018Mohanakumar et al, , 2019Mohanakumar et al, , 2020Mohanakumar et al, , 2021Rane et al, 2013;Rasmussen et al, 2010Rasmussen et al, , 2021Rasmussen et al, , 2022Saito et al, 2015;Tan et al, 2011;Telinius et al, 2010Telinius et al, , 2015Telinius et al, , 2017Telinius, Baandrup, et al, 2014;Telinius, Mohanakumar, et al, 2014;Unno et al, 2010;Yamamoto et al, 2014) met the inclusion criteria, see Figure 1. Of these, 20 were in vivo studies, seven were ex vivo and one study contained both in vivo and ex vivo data.…”
Section: Resultsmentioning
confidence: 99%